The myth of equality: Sexual harassment behind a woman’s desk - Joko Sampurno, Rahmad Darmawan (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2024)
Sexual harassment is a significant problem in employment but is often underreported. Women are one of the most vulnerable groups to get harassment in the workplace. As well as gender inequality towards women in development, which is caused by patriarchal cultural factors, such as men are always placed above women. Sexual harassment in the work environment does not only refer to physical acts but to unwanted verbal behavior, which makes the victim feel uncomfortable. This study aims to determine the harassment that occurs in the work environment. Besides, this study also aims to show that sexual jokes during breaks, even in meetings or workspaces at a telecommunication company, are considered normal. This study used qualitative methods with five subjects. These subjects are female workers at a company in Surabaya. They were chosen based on their sexual harassment experience. The research used accidental sampling to determine the subject. This study used a semi-structured interview data collection method. This study is analyzed in the theory of power relations. The theory of power relations stands on two things: (1) the power spreads everywhere (dispersed) and cannot be localized, and (2) when there are structures and relationships between people, there is power. The result demonstrated in three founds. There are several sexual harassments that occurred in the work environment, the resistance of female workers, and the challenges they faced in carrying out their work. Sexual harassment that occurs is verbally based and disguised as a joke in the work environment.